2020
DOI: 10.3390/polym12112447
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Films Based on Carboxymethylated Derivatives of Starch and Cellulose

Abstract: The carboxymethylated derivatives of starch (CMS) and cellulose (CMC) were used for film preparation. The infrared spectroscopy revealed that crosslinking via ester bridges with citric acid occurred between the two polysaccharide derivatives. The effect of polysaccharide derivatives ratio on physicochemical properties of prepared films was evaluated. Generally, the values of tested parameters (moisture absorption, surface roughness, and mechanical and thermal properties) were between the values noted for neat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
1
20
2
Order By: Relevance
“…Abral et al [ 73 ] showed that the opacity of biocomposites formed by cassava starch, polyvinyl alcohol (PVA), and BC increased according to the BC fiber concentration in the polymeric blend. Wilpiszewska et al [ 74 ] observed that films based on carboxymethylated derivatives of starch and cellulose were transparent and elastic; however, Santos et al [ 75 ] demonstrated that biocomposites of thermoplastic corn starch and BC showed a lower transparency than pure BC, different results from those found in our study. It is important to highlight that using a transparent wound dressing allows the patient to assess the wound healing process continuously without stimulating the injured area, thus reducing the probability of secondary injuries, particularly in cases of dermal lesions [ 76 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Abral et al [ 73 ] showed that the opacity of biocomposites formed by cassava starch, polyvinyl alcohol (PVA), and BC increased according to the BC fiber concentration in the polymeric blend. Wilpiszewska et al [ 74 ] observed that films based on carboxymethylated derivatives of starch and cellulose were transparent and elastic; however, Santos et al [ 75 ] demonstrated that biocomposites of thermoplastic corn starch and BC showed a lower transparency than pure BC, different results from those found in our study. It is important to highlight that using a transparent wound dressing allows the patient to assess the wound healing process continuously without stimulating the injured area, thus reducing the probability of secondary injuries, particularly in cases of dermal lesions [ 76 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The majority of food packaging materials used at present are based on petrochemical products or cellulose, due to historical factors such as low cost or mechanical and barrier properties [1,2]. The pressure of environmental concerns will phase out the petroleumbased materials, which will increase the need for innovative, biodegradable polymeric packaging materials such as chitosan [3], alginate [4], cellulose [5], starch [6], pullulan [7], polylactic acid [8], etc. The need to decrease the food waste, and the desire to increase the food safety and to prolong the shelf life creates pressure on the food packaging industry to develop and adopt new antimicrobial materials [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental pollution concerns have raised awareness and research regarding biodegradable polysaccharide-based food packaging material in the last decade [1,2]. Polysaccharide molecules are not only easily available and cheap, but they also form a continuous network by hydrogen bonding [3].…”
Section: Introductionmentioning
confidence: 99%